Optically induced abnormal terahertz absorption in black silicon - 翟东为;刘海玲;Xxx Sedao;杨玉平 (Chinese physics B, 2018)
The absorption responses of blank silicon and black silicon（silicon with micro/nano-conical surface structures） wafers to an 808-nm continuous-wave（CW） laser are investigated at room temperature by terahertz time-domain spectroscopy. The transmission of the blank silicon shows an appreciable change, from ground state to the pump state, with amplitude varying up to 50%, while that of the black silicon（BS） with different cone sizes is observed to be more stable. Furthermore,the terahertz transmission through BS is observed to be strongly dependent on the size of the conical structure geometry.The conductivities of blank silicon and BS are extracted from the experimental data with and without pumping. The non-photo-excited conductivities increase with increasing frequency and agree well with the Lorentz model, whereas the photo-excited conductivities decrease with increasing frequency and fit well with the Drude–Smith model. Indeed, for BS, the conductivity, electron density and mobility are found to correlate closely with the size of the conical structure.This is attributed to the influence of space confinement on the carrier excitation, that is, the carriers excited at the BS conical structure surface have a stronger localization effect with a backscattering behavior in small-sized microstructures and a higher recombination rate due to increased electron interaction and collision with electrons, interfaces and grain boundaries.